In-field runoff and soil water storage on duplex soils at Paradys Experimental Farm - Bothma, C. B. (University of the Free State, 2011)
The in-field rainwater harvesting tillage technique (IRWH), developed by the Agriculture Research Council (ARC), has been scientifically tested on clay soils at Glen Agricultural Institute by comparing with conventional tillage (mould board and disc ploughing). They showed that the IRWH crop production technique is by far more sustainable than conventional tillage. Great progress was made with the transfer of the information to rural communities located in the Thaba Nchu district. More than a thousand households applied IRWH in their homesteads during a period of three seasons of extension. According to socio-economic surveys, IRWH contributed significantly to reduce the risk of food insecurity at household level. Some of families who had access to tractors and implements identified the need to apply the IRWH on their crop fields. A tillage workshop was held at Merino village in November 2003 where several implements were demonstrated, but no-one implement was able to create the well-known surface structure of the IRWH to the satisfactory of the community. Hence, the first part of the study was designed to develop and test tractor drawn implements as a primary step for out scaling the IRWH technique. Several tractor drawn implements were designed and tested in collaboration with Bramley Engineering Company. Only two implements were further tested, viz. the ridge plough designed as a primary tillage tool for creating zero gradient contour rides, and the puddler plough designed as a secondary tillage tool for preparing the micro-basins along the ridge. These implements were demonstrated at Paradys Experimental farm of the University of the Free State to communal farmers, which indicated that the implements are acceptable to them. A land preparation procedure was developed for cultivating crop field sizes up to 150 ha in association with small scale farmers. Standard practices applied in zero tillage for weeding and pest control was adopted for IRWH. Maize was harvested with a combine harvester equipped with precision technology. Unfortunately maize planting commenced late due to the severe drought and was then disrupted by long periods of continuous rain, typical of semi-arid zones. Earlier planting areas gave yields up to 4500 kg ha-1, which provide ample proof that economical yields can be obtained on 50 – 150 ha crop fields. The study concludes that it is possible to commercialize the IRWH crop production technique and hence demonstrates the bio-physical view point that it is possible for communal and small scale farmers to practice IRWH on their crop fields. The second part of the study focused on variation in soil properties associated with the soil water storage on crop fields. For this study a 55 ha crop field under IRWH was used. Soils of the field were surveyed and the area was divided into 75 plots of equal size. These plots were used to take soil samples and soil water content. The pipette method was used for determining the clay and silt fractions of the 300 mm soil layers, while the neutron soil water meter was used for measuring the water content in the same layers. A mobile EM38, linked to a global positioning system, was used to estimate soil properties (clay plus silt content and soil water content) from the correlation between EM readings (electrical conductivity; EC, mS m-1) and the measured variables obtained in selected plots. The results showed reasonable good relationships between the EC and clay plus silt content, which allowed the estimation of a textural based management zones for the crop field. The textural relationship was further exploited to estimate the profile available water capacity (PAWC) and hence the delineation of PAWC management zones. A good correlation between EC and soil water content for the profile was obtained, which laid the foundation to estimate soil wetness spatially over the crop field. Thus, this part of the study provided conclusive evidence that it is possible to estimate the variation in soil water storage with electromagnetic induction methods. Hence it opens a new and exciting research field in soil water management that will change the landscape of precision farming in the next decade. It is envisaged that variation in soil water will be managed more intensively over large fields, especially in semi-arid zones, to optimize inputs related fertilization, planting rates, pests and weed control. The last objective of the study was to improve our understanding of how rainfall characteristics and soil physical properties influence the partitioning of rain into infiltration and runoff in the IRWH system. A mobile rainfall simulator was used to simulate rain storms of three different intensities, viz. low (33 mm h-1), medium (59 mm h-1) and high (122 mm h-1). Results obtained from the experiment demonstrated the importance of the influence of rain intensity on the infiltration parameters, such as time to runoff, time to final infiltration rate and final infiltration rate. The correlation matrix and multiple regression statistics make it possible to characterize the interaction between rainfall intensity and soil physical properties to predict the various infiltration parameters. From the infiltration-runoff relations it was clear that these soils exhibit a high potential to harvest water as required by the IRWH system. This study left the researchers with the following research challenges, namely (i) the socio-economic factors associated with the application of the mechanized IRWH technique at farm scale and (ii) the application of the EM38 to estimate soil wetness and other chemical properties in a wider range of soils and conditions.
Dissertation (M.Sc. Agric. (Soil, Crop and Climate Sciences))--University of the Free State, 2009
Keywords: Water harvesting -- South Africa -- Glen; Conservation tillage; Irrigation -- South Africa -- Glen